Equilibrium partitioning approach to define sediment quality guideline of some metals in Chao Phraya estuary - Thanakorn Jiwarungrueangkul (Chulalongkorn University, 2012)
This study aims to define numerical sediment quality guideline (SQG) based on equilibrium partitioning approach (EqP approach) that represents availability of metals in Chao Phraya estuarine sediment. The numerical SQG was calculated from the sediment-interstitial water partition coefficient (KD) in conjunction with Thai coastal water quality standards. In addition, the metals bound with sulfide fraction were taken into account in calculating the SQG because this fraction is potentially available to interstitial water when reoxidation process occurs in anoxic sediment. The KD was calculated from dividing metal concentrations extracted from the labile phase of sediment by metal concentrations in the interstitial water. The metals in labile phase were used for calculating the KD due to remobilization of this fraction in the sediment-interstitial water system as a result of changing physicochemical condition in sediment. The labile metals in sediment were extracted using 25% (v/v) acetic acid and calculated on the basis of size normalization and carbonate free basis. The SQG values for cadmium, copper, lead and zinc were found in the range of 1.2–3.1, 7–105, 23–86, and 16–125 mg kg-1 dry weight in <63µm fraction and CaCO3 free basis, respectively. The SQG values represented concentrations of potentially available metals in sediment. However, in order to support the calculated SQG values, toxicity test for metals using the local sediments should be further studied.